2021
DOI: 10.1002/bsl.2512
|View full text |Cite
|
Sign up to set email alerts
|

Wanting sex and willing to kill: Examining demographic and cognitive characteristics of violent “involuntary celibates”

Abstract: Over the past several years, an online community of self‐described “incels,” referring to involuntary celibates, has emerged and gained increased public attention. Central to the guiding incel ideology and master narrative are violent misogynistic beliefs and an attitude of entitlement, based on male gender and social positioning, with respect to obtaining desired and often illusory sexual experiences. While violence and hate speech within the incel community are both common, there exists a notable subset of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…In 2018, Nikolas Cruz killed 17 students and injured 17 more on Valentine's Day, having previously posted online 'Elliot Rodger will not be forgotten' and complaining about his isolation (Hoffman 2020). This was followed by Alek Minassian's van attack in Toronto in 2018, resulting in the deaths of 10 female victims and injury to another 16 (Williams 2021). It was later revealed that Minassian had hailed Elliot Rodger as his hero (Speckhard 2021) and explained that following Rodger's attack he felt proud and radicalised, stating that it was 'time to take action rather than fester in his own sadness' (Regehr 2022).…”
Section: Incels Violence and Mental Illnessmentioning
confidence: 99%
See 3 more Smart Citations
“…In 2018, Nikolas Cruz killed 17 students and injured 17 more on Valentine's Day, having previously posted online 'Elliot Rodger will not be forgotten' and complaining about his isolation (Hoffman 2020). This was followed by Alek Minassian's van attack in Toronto in 2018, resulting in the deaths of 10 female victims and injury to another 16 (Williams 2021). It was later revealed that Minassian had hailed Elliot Rodger as his hero (Speckhard 2021) and explained that following Rodger's attack he felt proud and radicalised, stating that it was 'time to take action rather than fester in his own sadness' (Regehr 2022).…”
Section: Incels Violence and Mental Illnessmentioning
confidence: 99%
“…However, hopelessness is not enough to trigger extreme violence among those incels who transition from depression and loneliness to a mission-oriented plan to ‘punish’ those they deem responsible for their frustrations (van Brunt 2021). Hopelessness, significantly exacerbated by cognitive distortions such as over-generalisations, all-or-nothing thinking (across multiple contexts), misattributions, lack of empathy, neutralisation and victim stances, provides a justification for subsequent acts of extreme violence (Williams 2020, 2021). In all attacks by incels, perpetrators misattributed blame to women for frustrations in their life, specifically for sexual frustration (Murray 2017; Williams 2020).…”
Section: The Current Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Research suggests incels celebrate mass murders as a means to recruit other men, to justify their violence, and to situate violence as a means to achieve policy changes that benefit men (Baele, Brace & Coan, 2019;O'Donnell & Shor, 2022;Sugiura, 2021). Indeed, Minassian, who murdered 11 people, claimed his violence was inspired by online incel discourse (Williams et al, 2021). We advance this literature by demonstrating how incels use Lépine to justify their violence and position themselves as both hegemonic killers and subordinate victims (Connell, 1995).…”
Section: Incels the Manosphere And Violencementioning
confidence: 99%